Super-hydrophobic organic-inorganic composite oxygen permeation membrane, preparation method thereof and application of super-hydrophobic organic-inorganic composite oxygen permeation membrane in lithium-air battery
By depositing a candle carbon nanoparticle layer on the surface of the PDMS film of the lithium-air battery, a superhydrophobic organic-inorganic composite oxygen permeable membrane was prepared, which solved the problem that the existing oxygen permeable membrane was difficult to maintain the long-term operation of the lithium-air battery, and achieved the The film has high mechanical stability and low cost preparation, suitable for high energy density batteries.
Patent Information
- Application Number
- CN202411349720.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium-air battery oxygen-permeable membrane is difficult to maintain the long-term operation of the battery, the preparation process is complex, the cost is high, and the environment is polluted, which limits the practical application of lithium-air batteries.
The superhydrophobic organic-inorganic composite oxygen-permeable membrane is used to deposit a layer of candle carbon nanoparticles on the surface of the PDMS membrane to improve the hydrophobic performance and mechanical stability of the membrane, thereby slowing down the invasion of moisture in the air and providing sufficient oxygen.
The long-term operation of lithium-air batteries is achieved, the mechanical stability and self-cleaning of the membrane are improved, the preparation cost is reduced, and the pollution to the environment is reduced.
Smart Images

Figure CN119481053A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a super-hydrophobic organic-inorganic composite oxygen-permeable membrane and a preparation method thereof and application in a lithium-air battery, belonging to the technical field of lithium-air batteries. Background Art
[0002] As one of the most promising power source candidates, rechargeable lithium-air batteries have an ultra-high theoretical energy density. They are composed of negative electrode metal lithium, porous positive electrode and non-aqueous electrolyte. Although its semi-open system is conducive to the entry of active material oxygen, impurities such as H2O and CO2 will cause serious side reactions with lithium, generate byproducts that are difficult to decompose, and accelerate the degradation of battery performance. When developing waterproof lithium-air batteries, trying to use hydrophobic oxygen-permeable membranes as protective barriers is an inevitable step in realizing practical lithium-air batteries. Although there have been many recent reports on the application of polydimethylsiloxane (PDMS) in lithium-air battery oxygen-permeable membranes, most oxygen-permeable membranes are difficult to maintain long-term operation of the battery, the preparation process is complicated, the cost is high, and there is a certain degree of pollution to the environment, which limits the practical application of lithium-air batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a super hydrophobic organic-inorganic composite oxygen permeable membrane and a preparation method thereof and application in lithium-air batteries. By depositing a candle smoke carbon nanoparticle layer on the surface of the PDMS membrane, the membrane has excellent hydrophobic properties and mechanical stability, and can slow down the invasion of moisture in the air at various relative humidities while providing sufficient oxygen for the battery to maintain long-term operation of the battery.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: A super-hydrophobic organic-inorganic composite oxygen-permeable membrane comprises a PDMS membrane and a carbon layer (CS deposition layer) deposited on at least one of the upper surface and the lower surface of the PDMS membrane.
[0005] The method for preparing the super hydrophobic organic-inorganic composite oxygen permeable membrane is to prepare the PDMS membrane and place it in a combustion gas production area of solid higher alkanes to deposit carbon to obtain the super hydrophobic organic-inorganic composite oxygen permeable membrane (PDMS-CS composite oxygen permeable membrane).
[0006] Preferably, the preparation method of the PDMS membrane is to mix PDMS and a curing agent to form a colloid, vacuum degassing and then spin coating to form a membrane, vacuum degassing and curing to obtain the PDMS membrane.
[0007] Preferably, the mass ratio of PDMS to curing agent is (8-15):1.
[0008] Preferably, the vacuum degassing conditions are: pressure 0.5-0.7 atm, 0.5-2 h.
[0009] Preferably, the conditions for preparing the PDMS film by spin coating are: rotation speed 0.5-5kr min -1 , rotate 10-120s.
[0010] Preferably, the vacuum degassing time is: 0.5-1.5h; The curing conditions are: 80-120°C, 0.5-1.5h.
[0011] Preferably, the PDMS membrane is placed in the center of the inner flame of the solid higher alkane for 5-20 seconds to deposit the candle smoke carbon. The molecular formula of the main component of the solid higher alkane is C n H 2n+2 , where n=17~35.
[0012] Application of the above-mentioned superhydrophobic organic-inorganic composite oxygen permeable membrane in lithium-air batteries.
[0013] A method for improving the mechanical stability of a lithium-air battery membrane is to place the lithium-air battery membrane preparation between the centers of a solid higher alkane inner flame to deposit candle soot carbon for 5-20 seconds, so as to form a candle soot carbon deposition layer on at least one of the upper surface and the lower surface of the lithium-air battery membrane; Among them, the membrane used for lithium-air batteries is a PDMS membrane.
[0014] The beneficial effects of the present invention are: The prepared PDMS-CS composite oxygen permeable membrane has excellent superhydrophobicity, a water contact angle of 163.2°, and excellent mechanical stability. It can keep the CS deposited layer from falling off after 60,000 bending tests. It also has self-cleaning properties, and there are no defects on the surface after 5 minutes of water flow impact, which improves the shortcomings of the CS deposited layer that is fragile and easy to be damaged, making it a strong and flexible superhydrophobic film. In the preparation process, the thickness of PDMS can be controlled by controlling the rotation speed, and the thickness of the CS deposited layer can be controlled by the deposition time; Furthermore, the prepared PDMS-CS composite oxygen permeable membrane can provide sufficient oxygen for lithium-air batteries and has good performance at different current densities. It is very helpful for the practical application of lithium-air batteries to exert their high specific capacity, which is very helpful for the development of high energy density batteries. It can also provide sufficient oxygen for the battery while slowing down the invasion of moisture in the air at various relative humidities to maintain the long-term operation of the battery. It provides a potential field for electric vehicles, energy storage systems and other fields that require long time and high energy density, thereby promoting its commercialization and popularization. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1(a) Schematic diagram of the preparation of PDMS-CS membrane; (b) Schematic diagram of the microstructure of PDMS-CS membrane; (c) SEM image of PDMS substrate membrane; (d) SEM cross-sectional view of PDMS-CS membrane; (e) SEM image of CS deposition layer; Figure 2 Optical images and water contact angles of PDMS membrane and PDMS-CS membrane; Figure 3 (a) XPS characterization of PDMS-CS film; (b) XRD characterization of CS layer deposited at different flame positions; (c) Raman characterization of CS layer deposited by internal flame; (d) Raman characterization of CS layer deposited by tip flame; Figure 4 The bending test images of PDMS-CS membrane and CS layer; Figure 5 (a) water flow impact test device; (b) image of changes in CS deposition layer after water flow impact; (c) image of changes in PDMS-CS film deposition layer after water flow impact; (e) water droplet sliding and self-cleaning test of PDMS substrate; (f) water droplet sliding and self-cleaning test of CS deposition layer; (g) water droplet sliding and self-cleaning test of PDMS-CS film deposition layer; Figure 6 PDMS-CS membrane and PDMS membrane protected lithium sheet at 95±5% relative humidity; Figure 7 Impedance changes of lithium-air batteries with (a) PDMS-CS membrane (b) PDMS membrane (c) no membrane protection at 95±5% relative humidity; (d) their ohmic impedance-time comparison; Figure 8 (a) Rate test of PDMS-CS membrane, PDMS membrane and lithium-air battery without membrane protection at 60±5% relative humidity; (b) Specific capacity test of PDMS-CS membrane, PDMS membrane and lithium-air battery without membrane protection at 95±5% relative humidity; Fig. 9 (a) Constant current charge and discharge test of PDMS-CS membrane, PDMS membrane and lithium-air battery without membrane protection at 45±5% relative humidity; (b) Constant current charge and discharge test of PDMS-CS membrane, PDMS membrane and lithium-air battery without membrane protection at 65±5% relative humidity; (a) Constant current charge and discharge test of PDMS-CS membrane, PDMS membrane and lithium-air battery without membrane protection at 95±5% relative humidity. DETAILED DESCRIPTION
[0016] Incomplete combustion is deliberately induced by blocking the flame of the candle, and nano-sized super-hydrophobic carbon nanoparticles are produced on the PDMS substrate, thereby constructing a strong super-hydrophobic oxygen-permeable membrane (PDMS-CS membrane) with economic benefits. The membrane is used in coordination with PDMS and CS, not only improving the shortcomings of poor mechanical stability of candle smoke carbon-based materials, but also inheriting the essential oxygen permeability of PDMS. Here, the present embodiment studies the surface morphology, chemical composition, wetting behavior and mechanical stability of the PDMS-CS membrane in detail. In addition, the assembled lithium-air battery can achieve long-term operation in the earth's atmosphere, show good battery performance, be conducive to the conservation and recycling of resources, and lay the foundation for the development of theoretical lithium-oxygen batteries to actual lithium-air batteries.
[0017] Synthesis of polydimethylsiloxane (PDMS) thin films.
[0018] First, PDMS and curing agent were mixed at a mass ratio of 10:1, and then vacuum was maintained at 0.7 atm at room temperature until the bubbles in the colloid were completely eliminated. Next, an appropriate amount of PDMS was poured on the surface of the glass sheet and the curing agent was mixed at a mass ratio of 10:1. Then, vacuum was maintained at 0.7 at room temperature until the bubbles in the colloid were completely eliminated. -1 The film was then degassed for 1 h under vacuum and cured at 100 °C for 1 h. The thickness of the prepared PDMS film was about 80 μm ( Figure 1 ).
[0019] Candle soot carbon (CS) composited with PDMS.
[0020] like Figure 1 As shown in the figure, a candle with a size of 10×5 cm (L×D) was placed in a perforated polyvinyl chloride plastic chamber, and the PDMS film was placed between the height centers of the candle flame. Candle smoke carbon (CS) was deposited for 10 seconds to obtain a CS layer with a thickness of about 20 μm ( Figure 1 ).
[0021] After CS deposition, a uniform porous network structure composed of CS nanoparticles was loaded on the smooth surface of the pure PDMS sample. This porous network structure is conducive to the embedding of the air cushion, reduces the liquid-solid interface area, and induces a typical Cassie-Baxter contact at the gas-liquid-solid interface. Figure 2 As shown, the transparent PDMS film can only show a contact angle of 110.4°, and its hydrophobic property is not strong, while the PDMS-CS black opaque film after CS deposition has a super hydrophobic contact angle of 163.2°.
[0022] It should be noted that the CS deposited layer prepared in this embodiment is deposited at the inner flame. Although the CS layers deposited at different flame heights have similar compositions, their intrinsic properties are different. The inner flame is located in the middle area of the candle flame, which is higher in temperature than the blue flame just above the wick. In this oxygen-deficient area, the flame is yellow, and the wax vapor evaporated at the wick can only be partially oxidized. Therefore, the candle smoke carbon deposited here not only contains carbon nanoparticles obtained by combustion, but also a large amount of hydrocarbons that are not fully oxidized. The temperature at the tip flame is higher and the oxygen is more sufficient, so the oxidation reaction is also the most complete, and the CS layer obtained here has more carbon nanoparticles and fewer hydrocarbons that are not fully oxidized.
[0023] The elemental composition of the PDMS-CS composite film obtained at different flame positions was detected by XPS and XRD. Figure 3 Areas a and b show that the two samples have the same phase composition. The Si element in XPS comes from PDMS. The strong broad peak at about 25° in the XRD spectrum is the property of amorphous materials, while the strong diffraction peaks at 44° and 78° indicate the presence of a small amount of carbon nanotubes in the sample. In addition, the diffraction peaks at 38° and 66° indicate incompletely burned paraffin compounds in the sample. It can be concluded that the CS layers deposited by the inner flame and the tip flame are both obtained from carbon and partially oxidized wax vapor. The next step is to further analyze the intrinsic properties of CS at different flame positions using Raman. From Figure 3 It can be seen from the c and d regions that the ID / IG value of the CS deposited by the inner flame is 1.13, indicating that it has a high amorphous carbon content, a rough surface and many defects. The ID / IG value of the CS deposited by the tip flame is 0.97, indicating that it has a higher degree of graphitization and the paraffin vapor is more fully oxidized. This is because the inner flame usually has a lower temperature, lower oxygen concentration and more complex chemical reactions than the tip flame, which is conducive to the adsorption of incompletely burned hydrocarbons and the rapid cooling of CS after deposition, making it show higher hydrophobicity.
[0024] However, the CS nanoparticle layer is easy to fall off, which can easily cause damage to the hydrophobic layer during the long-term cycle of the battery, thereby causing the battery to die prematurely. The PDMS-adhered CS (PDMS-CS) prepared in this embodiment can greatly enhance the mechanical stability and bonding force of the CS layer. Figure 4 As shown in the figure, after 60,000 bends, the PDMS-CS still has no cracks on the surface, indicating that PDMS can firmly adhere to CS. However, after 60,000 bends, the CS deposition layer without PDMS as a substrate has a large number of cracks on the surface.
[0025] like Figure 5In the middle ac region, PDMS-CS can withstand the impact of water flow for five minutes while keeping the surface of the deposited layer intact and free of defects. In contrast, the CS deposited layer without PDMS as a substrate was broken down after only two minutes of water flow impact. In addition, when water droplets were dripped on the sample, it was found that PDMS-CS had good self-cleaning properties and the CS deposited layer was not easy to fall off ( Figure 5 This further proves its good mechanical stability.
[0026] In order to prove that the prepared PDMS-CS can help lithium-air batteries operate for a long time in a high humidity environment, two glass bottles containing lithium sheets of the same size were sealed with PDMS-CS and PDMS, respectively, and 30 μL of water was dropped on the surface of the film sample to observe its changes. Figure 6 As shown in the figure, the lithium sheet protected by PDMS turned slightly black after 15 minutes, while the lithium sheet protected by PDMS-CS had a good metallic luster. As time went on, the lithium sheet protected by PDMS became darker and darker. At 450 minutes, the lithium sheet had completely turned black, while the lithium sheet protected by PDMS-CS still had a certain metallic luster. This shows that the PDMS-CS film can greatly slow down the degree of water erosion of metallic lithium, and is expected to achieve long-range cycling of lithium-air batteries under high humidity.
[0027] Preparation of lithium-air batteries.
[0028] The air cathode of the lithium-air battery was made by rolling a slurry containing Super P catalyst and PTFE polymer binder (weight ratio of 85:15) on carbon paper, and sealed into a coin cell with or without an oxygen permeable membrane (H2O < 0.1 ppm; O2 < 0.1 ppm) in an Ar-filled glove box.
[0029] After assembly, the button-type lithium-air battery was placed in an unsealed test jar, and the relative humidity value during the test was monitored by a digital hygrometer. In addition, for the test condition of relative humidity ~95±5%, 5 mL of water was applied to the bottom of the test jar to maintain a constant relative humidity. The battery was left to stand for 10 hours before measurement.
[0030] Electrochemical impedance spectroscopy (EIS) was used to detect the impedance changes of the assembled lithium-air battery when placed in a high relative humidity of ~95±5%. An equivalent circuit was established for quantitative analysis of the Nyquist plot, where R e represents the current collector resistance and electrolyte resistance, R int Refers to the interfacial impedance between the liquid electrolyte and the metallic lithium electrode (high frequency first relaxation semicircle), R c Refers to the charge transfer resistance (mid-frequency semicircle),W 0 Refers to the diffuse resistance Warburg impedance (low frequency linear tail). Figure 7 The middle a area shows that the battery protected by PDMS-CS can be exposed to high humidity air for a long time and presents a relatively low impedance. Even at 48 h, the impedance is only 649Ω, indicating that the film has good moisture resistance. Under the same conditions, both the battery protected by PDMS and the lithium-air battery without membrane protection showed a significant increase in impedance. Both increased from 397 and 383Ω to 611 and 3447Ω respectively after 24h, and continued to increase to 1256 and 20185Ω respectively after 48h. In particular, the EIS spectrum of the battery without membrane protection at 48h can only observe a huge Warburg impedance, while the electrode / electrolyte interface impedance in the high-frequency region can no longer be observed, which means that the lithium metal negative electrode has been severely corroded by the moist O2 in the air, and the electrode / electrolyte interface is destroyed by solid byproducts such as LiOH, and ion diffusion is difficult. Therefore, the PDMS-CS prepared in this embodiment is a potential good waterproof barrier that can effectively resist the invasion of water molecules.
[0031] In general, the O2 permeability value determines the rate performance of Li-air batteries. To evaluate the O2 permeability, Li-air batteries with PDMS-CS, PDMS, and no membrane protection were tested at 1000 mAh g -1 Constant cut-off capacity of 200, 500, 1000 and 1500 mA g -1 Current density, rate test at 60±5% relative humidity ( Figure 8 The results show that PDMS-CS not only has good moisture resistance, but also inherits the high oxygen permeability of PDMS, and does not lead to poor rate performance due to the deposition of CS. In addition, in the capacity test conducted at a high relative humidity of 95±5%, the battery protected by PDMS-CS has a capacity of 4649.5mAh g -1 The specific capacity of PDMS-CS is much higher than that of the other two batteries, which further illustrates the excellent oxygen permeability and moisture resistance of PDMS-CS. -1 It decays rapidly at low current density and has a very low specific capacity (306.59 mAh g -1 ), indicating the huge impact of impurities in the air on battery performance.
[0032] For practical lithium-air batteries, long cycle life means that the battery can undergo more charge and discharge cycles, thereby providing more power in the same amount of time, which helps to improve energy efficiency and reduce energy waste. Fig. 9As shown in the figure, the battery was subjected to constant current charge and discharge tests at different relative humidity. It can be seen that at a relative humidity of 45±5%, the PDMS-CS protected battery was able to -1 , 1000 mAh g -1 The battery can run stably for 220 hours under low humidity, which is at least twice the total cycle time of the battery without membrane protection. In addition, in relatively humid weather (relative humidity of 65±5%), the battery protected by PDMS-CS can also run for about 175 hours, while the batteries protected by PDMS and without membrane protection reach the cut-off voltage of 2.0V at about 130 hours and 100 hours, respectively. It is worth mentioning that at a high relative humidity of 95±5%, the battery protected by PDMS-CS can also maintain battery operation for 75 hours. The battery protected by PDMS decays in 50 hours, and the battery without membrane protection can only run for 4 hours. In general, by comparing the lithium-air batteries assembled with PDMS-CS, PDMS and without hydrophobic oxygen-permeable membranes at different humidity, the self-discharge impedance change, rate performance, specific capacity and long cycle performance of the battery are compared, which further confirms that the PDMS-CS hydrophobic oxygen-permeable membrane successfully slows down the transfer of moisture in the air to the inside of the battery, providing an effective template for the practical application of lithium-air batteries.
[0033] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the protection scope of the patent of the present invention.
Claims
1. A super-hydrophobic organic-inorganic composite oxygen permeable membrane, characterized in that: The method comprises a PDMS film and a carbon deposition layer deposited on the PDMS film, wherein the thickness of the carbon deposition layer is in the range of 5-50 μm.
2. The method for preparing the super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 1, characterized in that: After the PDMS membrane is prepared, it is placed in a combustion gas generating area of solid higher alkane to deposit carbon, thereby obtaining the super hydrophobic organic-inorganic composite oxygen permeable membrane.
3. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 2, characterized in that: The preparation method of the PDMS membrane is to mix PDMS and a curing agent to form a colloid, vacuum degassing and then spin coating to form a membrane, vacuum degassing and curing to obtain the PDMS membrane.
4. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 3, characterized in that: The mass ratio of PDMS to curing agent is (8-15):
1.
5. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 3, characterized in that: The conditions for vacuum degassing are: pressure 0.5-0.7atm, 0.5-2h.
6. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 3, characterized in that: The conditions for preparing the PDMS membrane by spin coating are: rotation speed 0.5-5kr min -1 , rotate for 10-120s.
7. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 3, characterized in that: Vacuum degassing time: 0.5-1.5h; The curing conditions are: 80-120°C, 0.5-1.5h.
8. The method for preparing a super-hydrophobic organic-inorganic composite oxygen permeable membrane according to claim 2, characterized in that: The PDMS membrane is placed in the center of the inner flame of the solid higher alkane for carbon deposition for 5-20 seconds. The molecular formula of the main component of the solid higher alkane is C n H 2n+2 , where n=17~35.
9. Use of the super-hydrophobic organic-inorganic composite oxygen-permeable membrane according to claim 1 in lithium-air batteries.
10. A method for improving the mechanical stability of a membrane for a lithium-air battery, characterized in that: The lithium-air battery membrane is placed in the center of the solid higher alkane inner flame to deposit carbon for 5-20 seconds to form a carbon deposition layer on the lithium-air battery membrane; Among them, the membrane used for lithium-air batteries is a PDMS membrane.